Weight bias internalization and health: a systematic review. (22nd May 2018) - Pearl, R. L.; Puhl, R. M.
Summary: A robust literature has documented the negative health effects of being the target of weight bias. Weight bias internalization (WBI) occurs when individuals apply negative weight stereotypes to themselves and self‐derogate because of their body weight. Compared with experiences of weight bias, less is known about the relationship between WBI and mental and physical health, although more literature on this topic has emerged in recent years. The current systematic review identified 74 studies assessing the relationship between WBI and health and interventions designed to reduce WBI and improve health. Over half of identified studies were published from 2016 to 2017. Results showed strong, negative relationships between WBI and mental health outcomes. Fewer studies have examined the relationship between WBI and physical health, and results were less consistent. Key directions for future research are highlighted, including the need for prospective and experimental studies with greater sample diversity.